Admission policies for a two class loss system - Örmeci, EL; Burnetas, A; Van Der Wal, J. (Communications in Statistics. Part C: Stochastic Models, 2001)
We consider the problem of dynamic admission control in a Markovian loss queueing system with two classes of customers with different service rates and revenues. We show that under certain conditions, customers of one class, which we call a preferred class, are always admitted to the system. Moreover, the optimal policy is of threshold type, and we establish that the thresholds are monotone under very restrictive conditions. Copyright © 2001 by Marcel Dekker, Inc.